Development of on-board Intelligent Display Terminal Based on ARM & WinCE - 杨宁; 王立德; 王苏敬; 丁国君 (机车电传动)
An on-board intelligent display terminal based on ARM and WinCE was given for the technological reform of electric locomotive. The article analyzed the current locomotive display terminal’s needs on the Graphical user interface, real-time network communications, and fault record, completed hardware and software design of display terminal, expounded the idea and design method of software.